2020
DOI: 10.1016/j.hemonc.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Characteristics of Acute Promyelocytic Leukemia Translocation Variants

Abstract: Acute promyelocytic leukemia (APL) is a special disease entity of acute myeloid leukemia (AML). The clinical use of all-trans retinoic acid (ATRA) has transformed APL into the most curable form of AML. The majority of APL cases are characterized by the fusion gene PML-RARA. Although the PML-RARA fusion gene can be detected in almost all APL cases, translocation variants of APL have been reported. To date, this is the most comprehensive review of these translocations, discussing 15 different variants. Reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 106 publications
1
18
0
1
Order By: Relevance
“…Abnormal changes of autosomal karyotypes were more common in S-AML patients and were closely related to survival prognosis. Studies have shown a more incidence of abnormalities on chromosomes 5 and 7 in patients with S-AML [19,20]. In our study, 62.5% (10/16) abnormal chromosome karyotypes had abnormalities on chromosomes 5 and 7.…”
Section: Discussionsupporting
confidence: 57%
“…Abnormal changes of autosomal karyotypes were more common in S-AML patients and were closely related to survival prognosis. Studies have shown a more incidence of abnormalities on chromosomes 5 and 7 in patients with S-AML [19,20]. In our study, 62.5% (10/16) abnormal chromosome karyotypes had abnormalities on chromosomes 5 and 7.…”
Section: Discussionsupporting
confidence: 57%
“…APL constitutes a subgroup of AML (AML-M3) associated with the balanced reciprocal chromosome rearrangement of t(15;17)(q24;q21) that generates the fusion of PML and the RARA genes [ 80 , 81 ]. Both ATRA and ATO are effective agents for curing t(15;17) chromosomally translocated APL [ 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute promyelocytic leukaemia (APL) results from reciprocal translocation between chromosomes 15 and 17, t(15;17) (q24;q21) giving rise to chimeric fusion of oncogene; the promyelocytic leukaemia ( PML ) gene and cellular differentiation protein; and the retinoid acid receptor alpha ( RARA ) gene resulting in PML‐RARA fusion gene [ 3 ]. Normal PML is a tumour suppressor gene that is transcribed to PML tumour suppressor protein in the cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%